PENERAPAN COACHING OLEH ASISTEN SUPERVISOR DAERAH PT. MANDOM INDONESIA TBK DI MADURA - Farida Yuniati; Nuri Herachwati; Zainiyah Alfirdaus (LPSDI Bina Patria, 2023)
Human resources are one of the keys to the company's success in achieving the goals to be achieved. However, human resources in Madura are included in the low category. The Human Development Index (HDI) of four districts in Madura is in the top 10 lowest in East Java. HR in the company, in this case, employees not only need support when they succeed in achieving targets but when they fail to do so. The application of the coaching process can follow a flow/stage of a simple coaching model, with this model leaders will be helped to better coach their employees. A popular coaching process used is by using the flow/steps of THE COACH MODEL created by Keith E. Webb. The Coach Model consists of five stages, namely, Connect, Outcome, Awareness, Course, and Highlights. Regional Assistant Supervisor (ASD) is responsible for improving the performance and work performance of employees at the regional level. ASD with its leadership provides an important role to improve employee performance and also organizational performance through established policies and decisions. Efforts to improve the performance, competence and, work performance of employees aim to be able to achieve company goals effectively and efficiently. Leadership plays a dominant and crucial role in the overall effort to achieve goals. This study aims to determine the application of coaching by leaders to employees.